The Attitudes of Secondary Schools Headmasters of M’ssila toward the Subject of Physical and Sport Education and its relation to the motivation achievement of the teacher - marzougi samir (sports creativity, 2025)
The present study, entitled: "The Attitudes of Secondary Schools Headmasters of M’silatoward the Subject of Physical and Sport Education and its relation to the motivation achievement of the teacher". Aims at examining the co-relation between the attitudes of secondary schools headmasters of M’sila toward the Subject of Physical and Sport Education and the motivation achievement of the teacher. To this end, we adopted the correlational and the descriptive-analytical approaches, we have also used the survey method by applying two scales. The school administration scale trends toward Physical and Sport Education. To this end, and relying on a Sample Survey we have selected55Headmasters and the motivation achievement scale which has targeted a sample of102 teachers of Physical and Sport Education. After the statistical processing of Data, the study resulted in the following : 1 - The Headmasters trends in secondary schools of M’sila score positively towards the subject of physical and sport education on all three dimensions of the scale and the scale as a whole. 2 - The study confirmed that the Teachers of physical and sport education of M’sila have a high motivation achievement. 3 - There is no correlation between the Headmasters trends towards the subject of physical and sport education and the motivation achievement of the teachers, in secondary schools of M’sila